THE EXISTENCE OF HUMAN RIGHTS COURTS IN INDONESIA - Abdul Wahab Suwakil (Fox Justi : Jurnal Ilmu Hukum, 2020)
The main problem is How the Human Rights Court Existence in Law Enforcement in Indonesia, and the main problem is still further broken down into several sub-problems. What is the Profile of the Establishment of the Human Rights Court, How is the retroactive principle applied in the Human Rights Court to past human rights violations, and How is the existence of the Human Rights Court in law enforcement. In writing this thesis using descriptive writing methods, and using normative theological methods, normative juridical approaches, historical aspects approach, data collection methods in the form of library research, by reading, discussing and analyzing reference books, as well as in data processing and analysis methods using inductive and deductive methods. The Human Rights Court is an institution that hears and decides on any gross violation of human rights. In accordance with Law No. 26 of 2000 where every time there is a serious violation of human rights that occurs, then everything is processed in a human rights court, including crimes of genocide and crimes against humanity. The birth of this court was based on the will of the international community and Indonesia, where many human rights cases occurred in Indonesia so that this Human Rights Court was formed. The birth of Law no. 26 of 2000 concerning the Human Rights Court is a benchmark that Indonesia can try cases of Human Rights Violations itself without any outside interference. Many cases that have been tried in human rights courts in Indonesia are still very ineffective, both for all victims of cases of human rights violations committed by several individuals who have violated both past and present violations. The application of the retroactive principle in the Human Rights Court contradicts the Legality Principle adopted in the Indonesian Criminal Code. So that the effectiveness of this Human Rights Court still needs to be questioned and improved again in order to provide good things for the people in Indonesia. Many cases that have been tried in human rights courts in Indonesia are still very ineffective, both for all victims of cases of human rights violations committed by several individuals who have violated both past and present violations. The application of the retroactive principle in the Human Rights Court contradicts the Legality Principle adopted in the Indonesian Criminal Code. So that the effectiveness of this Human Rights Court still needs to be questioned and improved again in order to provide good things for the people in Indonesia. Many cases that have been tried in human rights courts in Indonesia are still very ineffective, both for all victims of cases of human rights violations committed by several individuals who have violated both past and present violations. The application of the retroactive principle in the Human Rights Court contradicts the Legality Principle adopted in the Indonesian Criminal Code. So that the effectiveness of this Human Rights Court still needs to be questioned and improved again in order to provide good things for the people in Indonesia. both to all victims of cases of human rights violations committed by several individuals who committed violations, both past and present violations. The application of the retroactive principle in the Human Rights Court contradicts the Legality Principle adopted in the Indonesian Criminal Code. So that the effectiveness of this Human Rights Court still needs to be questioned and improved again in order to provide good things for the people in Indonesia. both to all victims of cases of human rights violations committed by several individuals who committed violations, both past and present violations. The application of the retroactive principle in the Human Rights Court contradicts the Legality Principle adopted in the Indonesian Criminal Code. So that the effectiveness of this Human Rights Court still needs to be questioned and improved again in order to provide good things for the people in Indonesia